Implementasi Far East Law System Dalam Mekanisme Restorative Justice Di Indonesia Berbasis Civil Law - Aufan, Briely Daffa; Buana, Syahfa Rizi Rasta (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2023)
The implementation of the Far East Law System in the mechanism of Restorative Justice in Indonesia based on Civil Law is an interesting topic to be discussed in a journal. This journal will explore the application of the Far East Law System in the context of Restorative Justice in Indonesia, which is based on Civil Law. Restorative Justice is an approach that involves offenders, victims, and the community in achieving a more holistic form of justice and restoration. In the Indonesian context, the implementation of the Far East Law System can contribute to strengthening the mechanism of Restorative Justice by emphasizing principles such as reconciliation, peace, and recovery. This journal will explore how the implementation of the Far East Law System can influence the process of restoring justice in Indonesia, as well as identify the challenges and opportunities in implementing this legal system. It is hoped that this journal will provide valuable insights into how the integration of the Far East Law System and Restorative Justice can enhance the effectiveness of the judicial system in Indonesia